Answer:
The maximum value= 36
Minimum value = - 36
Explanation:
Given that
f(x, y, z) = 8 x + 8 y + 4 z
h(x,y,z)=4 x² + 4 y² + 4 z² - 36
From Lagrange multipliers
Δf = λ Δh
Δf = < 8 ,8 , 4>
Δh = < 8 x ,8 y , 8 z>
Δf = λ Δh
So
< 8 ,8 , 4> = < 8 λ x ,8 λ y , 8 λ z>
8 = 8 λ x -------------1
8 = 8 λ y ---- ------2
4 = 8 λ z ----------------3
From equation 1 ,2 and 3
Now by putting the value of x,y and z in the following equation
4 x² + 4 y² + 4 z² = 36
![4* (1)/(\lambda^2 )+4* (1)/(\lambda^2 )+4* (1)/((2\lambda)^2 )=36](https://img.qammunity.org/2020/formulas/mathematics/college/6tz6ewnswv1alajfazw6ruobrkp3ws3oel.png)
![(4)/(\lambda^2 )+ (4)/(\lambda^2 )+ (1)/(\lambda^2 )=36](https://img.qammunity.org/2020/formulas/mathematics/college/2hqmu89rnf80ikd0w0ga03fliweqhon635.png)
So the value of λ is
![\lambda =\pm (1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/college/ur2eofzfa72umb7y2u891zv15mnp2rskoj.png)
When λ = 1/2
x = 1 / λ , y=1 / λ , z= 1 /2 λ
x= 2 , y = 2 , z=1
So
f(x, y, z) = 8 x + 8 y + 4 z
f(2, 2, 1) = 8 x 2 + 8 x 2 + 4 x 1
f(2, 2, 1) =36
When λ = - 1/2
x = 1 / λ , y=1 / λ , z= 1 /2 λ
x= - 2 , y = - 2 , z= - 1
So
f(x, y, z) = 8 x + 8 y + 4 z
f(-2, -2, -1) = 8 x (-2) + 8 x (-2) + 4 x (-1)
f(-2, -2, -1) = - 36
The maximum value= 36
Minimum value = - 36